The ministry of reconciliation : a comparative study of the role of the churches in promoting reconciliation in South Africa and Angola - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD (Science of Religion and Missiology))--University of Pretoria, 2008.